Assessing policy robustness under the COVID-19 crisis: an empirical study of the environmental policymaking system in Ontario, Canada. Issue 6 (2nd November 2022) - Mirnasl, Nayyer; Philpot, Simone; Akbari, Aidin; Hipel, Keith W.
ABSTRACT: Desirable robust systems retain functional reliability and legitimacy in times of crisis and show minimal sensitivity to these events. As a multifaceted crisis, the COVID-19 pandemic posed various challenges to policymaking systems around the globe. In this study, the authors evaluate changes within the environmental policymaking system in Ontario, Canada, during this crisis and analyze them in light of the robust policy design literature and its links to the broader concept of policy design success and failure. These changes are evaluated using an empirical hypothesis testing approach designed to assess the variations of key indicators in the administrative and public participation domains of Ontario's environmental policymaking system during and before the COVID-19 pandemic. The results indicate that the system has failed to retain its functional reliability, and thus its robustness, during this crisis. The authors conclude by contextualizing these results in light of the more recent history of environmental policymaking in the province and its impacts on Ontario's environment and offering suggestions for future research building on this empirical example.